Impact of Information Technologies in the Agricultural Supply Chain: A bibliographical review - Cedano, Jose Manuel (2026)
This systematic review examined the impact of information technologies (IT) including IoT, blockchain, big data, artificial intelligence and cloud computing on agricultural supply-chain management between 2015 and 2025. Following PRISMA guidelines, searches in Scopus, Web of Science, SciELO and Redalyc combined descriptors for IT and agri-food logistics; rigorous inclusion/exclusion criteria reduced 1,034 records to 59 peer-reviewed articles. Evidence shows that IT enhances traceability, curbs losses and supports real-time decision making through sensors, analytics and smart contracts; blockchain-IoT synergies strengthen transparency, big-data analytics mitigates food waste, and time-temperature indicators extend meat shelf life. Nevertheless, infrastructural, financial and skill-related barriers—particularly in small and medium enterprises—hamper adoption and create gaps relative to large firms. It is therefore proposed that converging digital technologies represent a strategic lever for more efficient, resilient and sustainable agri-food supply chains, provided that supportive policies, data standards and capacity-building programmes are enacted